PENGARUH STRUKTUR MODAL, PROFITABILITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Silmi Kaffah, 13.05.51.0158 (Students' Journal of Economic and Management, 2017)
This study examines the effect of capital structure, profitability, firm size, and dividend policy on firm value. This research is conducted at Indonesia Stock Exchange by using a go public manufacturing company as the unit of analysis. Sampling method used purposive sampling with the observation period from 2012 to 2015. Relationship and (or) influence between variables is explained by using method of multiple regression analysis. The results showed that the capital structure, profitability, and firm size have a positive effect and significant on firm value. While the de-dividend policy has no significant effect on firm value. Keyword : Capital Structure, Profitability, Firm Size, Dividend Policy, and Firm Value.